Special papersRelationship between SYNTAX score and Trans-Atlantic Inter-Society Consensus II classification in patients undergoing diagnostic angiography - Erkan, Hakan; Vatan, Bülent; Tarik Agaç, Mustafa; Korkmaz, Levent; Erkan, Merve; Kiris, Abdulkadir; Acar, Zeydin; Çelik, Șükrü (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction: Peripheral artery disease (PAD) is a marker of systemic atherosclerosis and most patients with PAD also have concomitant coronary artery disease (CAD). Aim : There are no published data investigating the relationship between PAD and CAD complexity assessed by a well-accepted classification system such as the SYNTAX score (SS) or Trans-Atlantic Inter-Society Consensus II (TASC II). Material and methods: The study population consisted of 72 patients who underwent coronary angiography for the assessment of CAD. At the same session, peripheral angiography was performed in cases of suspected PAD. A coronary lesion was defined as significant if it caused a 50% reduction of the luminal diameter by visual estimation in vessels ≥ 1.5 mm. The SYNTAX score was computed by dedicated software. Results: Patients with peripheral artery disease were divided into four groups according to the Trans-Atlantic Inter-Society Consensus II classification. Numbers of patients with peripheral artery disease classified as A, B, C, and D by the Trans-Atlantic Inter-Society Consensus II classification were 27, 16, 18 and 11, respectively. SYNTAX scores for each group from A to D were 10 ±9, 11 ±10, 24 ±13 and 27 ±12, respectively; p for trend < 0.001. Conclusions : Higher Trans-Atlantic Inter-Society Consensus II classification is associated with higher SYNTAX score in patients who underwent coronary and peripheral diagnostic angiography. It may suggest that arterial atherosclerotic disease complexity is a systemic panvascular phenomenon.